Identifying Musculoskeletal Discomfort in a Manufacturing Plant in Los Olivos, Lima–Peru - Brunette, María Julia (2016)
This article describes the process of implementing a musculoskeletal worker survey in a worker manufacturing plant in Lima, Peru’s industrial capital. The questionnaire was designed following the principles of participatory ergonomics and respecting the various socio-cultural aspects of our target population.